Navigating AI and chatbot applications in education and research: a holistic approach - Abhishek N.; Sonal Devesh; Ashoka M.L.; Neethu Suraj; Parameshwara Acharya; Divyashree M.S. (Quality Education for All)
Purpose – This study aimed to identify factors influencing AI/chatbot usage in education and research, and to evaluate the extent of the impact of these factors. Design/methodology/approach – This study used a mixed approach of qualitative and quantitative methods. It is based on both primary and secondary data. The primary data were collected through an online survey. In total, 177 responses from teachers were included in this study. The collected data were analyzed using a statistical package for the social sciences. Findings – The study revealed that the significant factors influencing the perception of the academic and research community toward the adoption of AI/interactive tools, such as Chatbots/ChatGpt for education and research, are challenges, benefits, awareness, opportunities, risks, sustainability and ethical considerations. Practical implications – This study highlighted the importance of resolving challenges and enhancing awareness and benefits while carefully mitigating risks and ethical concerns in the integration of technology within the educational and research environment. These insights can assist policymakers in making decisions and developing strategies for the efficient adoption of AI/interactive tools in academia and research to enhance the overall quality of learning experiences. Originality/value – The present study adds value to the existing literature on AI/interactive tool adoption in academia and research by offering a quantitative analysis of the factors impacting teachers' perception of the usage of such tools. Furthermore, it also indirectly helps achieve various UNSDGs, such as 4, 9, 10 and 17.